Penerapan pembelajaran kitab Ta’limul Muta’allim terhadap pembentukan nilai –nilai akhlak santri Pondok Pesantren Darul Hijroh Sukoharjo - Ridwan Setiyono; Siti Rohimah; Meti Fatimah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This study aims to explore the implementation of Kitab Ta’limul Muta’allim learning in shaping moral values among students at Pondok Pesantren Darul Hijroh Sukoharjo. A qualitative approach was employed, collecting data through interviews and observations. The findings reveal that the implementation of Kitab Ta’limul Muta’allim learning is effective in shaping important moral values among students. Values such as piety, patience, honesty, and openness are developed through a deep understanding of Islamic teachings and practical application in daily life. The students responded positively to this learning approach and experienced changes in their attitudes and behaviors. This study provides a deeper understanding of the role of Kitab Ta’limul Muta’allim learning in shaping the character of students.